Assessment of administrative burden on South African Controlled foreign company rules relative to the imputation - Matlou, Tracy (University of the Witwatersrand, Johannesburg, 2022)
South African multinational enterprises must comply with the controlled foreign company (CFC) rules in section 9D of the Income Tax Act 58 of 1962 (the Act). The provisions of section 9D of the Act are collectively referred to in this document as CFC rules. The CFC rules are anti-avoidance provisions that discourage South African multinational enterprises from shifting income to foreign companies under their control. This study examines the administrative burden placed on South African multinational enterprises (MNEs) to comply with section 9D of the Act and assesses this administrative burden for reasonableness when compared to the amounts eventually imputed. The study investigates whether South African CFC (SA CFC) rules, which are complex, carry a significant administrative burden on South African MNEs. SA CFC rules are confusing and often are misunderstood by the South African multinational enterprises. This study compares SA CFC rules to the Organisation for Economic Co-operation and Development (OECD), Base erosion and profit shifting (BEPS) action 3’s recommendations for effective CFC rule
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Commerce (specialising in Taxation) Johannesburg, 2022
Keywords: UCTD; Administrative burden; Controlled Foreign Company rules; CFC; Net income; OECD; SARS; Section 9D; Income Tax Act; SDG-8: Decent work and economic growth